Transformation of Integrative Islamic Education Curriculum: The Synergy of Science, Technology, and Maqasid al-Shariah in Islamic Education - Hary Nurdi; Ani Cahyadi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This article examines the transformation of the integrative Islamic Education curriculum through the synergy of science, technology, and Maqasid al-Shariah within the broader context of contemporary Islamic education. The study aims to explore the philosophical foundations, conceptual models, implementation strategies, and educational implications of integrating scientific knowledge, technological advancement, and Islamic ethical principles into the Islamic Education curriculum. The research employs a qualitative approach using the Library Research method by analyzing classical Islamic scholarship, contemporary educational theories, curriculum studies, and recent scholarly publications related to Islamic education and educational technology. The findings reveal that the integration of science and technology with Maqasid al-Shariah creates a transformative educational paradigm that not only strengthens students’ intellectual competence but also develops spiritual awareness, ethical responsibility, and social sensitivity. The study further demonstrates that the curriculum transformation contributes to the development of holistic Muslim learners capable of responding to the challenges of globalization, digitalization, and technological disruption without losing Islamic identity and moral values. The novelty of this study lies in the formulation of a conceptual framework for an integrative Islamic Education curriculum based on the alignment between scientific literacy, digital competence, and the objectives of Islamic law.